Pengaruh Aktivitas Sosial terhadap Nilai Indeks Prestasi Kumulatif (IPK) Mahasiswa Fakultas Teknologi Dan Bisnis Energi Institut Teknologi PLN - Adilla Khairani; Dexa Tri Pramanda; Syachka Ghautsul Adhom; Luh Putu Veny Ratih Krisnandewi (Program Studi Teknik Industri Universitas Teknologi Sumbawa, 2025)
The Cumulative Grade Point Average (GPA) is a metric that shows the academic achievement of students during their studies. GPA can be influenced by various factors such as social activities carried out by students outside of study hours. This study aims to determine the difference in the average score of the Student Achievement Index (GPA) between students who have social activities and students who do not have social activities. The method used in data analysis is a 2-way ANOVA variance analysis (Two Way Analysis of Variance) in the SPSS Statistics 24 software. The results of the study show that the average score (means) of the GPA of Industrial Engineering students is 3.53, Mechanical Engineering 3.48 and Energy Business 3.78. Hypothesis 1 regarding the difference in average GPA between each major obtained a significant rate of 0.005 < 0.05. Hypothesis 2 regarding the difference in average GPA between socially active and socially inactive students obtained a significance level of 0.583 > 0.05 (sig 0.583 > 0.05). Hypothesis 3 regarding the interaction between the average GPA of students per department and activities was obtained with a significance level of 0.844 > 0.005 (sig 0.844 > 0.05). There was no difference in the results of the Student Achievement Index between students who were socially active and students who were not socially active.